(untitled) (Medical Forum Monthly, 2024)
Background: Dengue fever has emerged as an important public health problem in recent years and has become endemic throughout major cities in Pakistan. In Lahore, capital of Punjab it has appeared as an epidemic during last few years. Lahore has been worst hit by Dengue and emerged as an epidemic with terrible implications on health and economy of the populations and collapsing the health systems. Study was conducted during the peak of epidemic in 2011. Objectives: To establish a baseline of knowledge, attitude and practices for dengue prevention. Study Design: Cross Sectional Study. Place and Duration of Study: This study was conducted in Lahore, Capital of Punjab province. Lahore has been divided in to eight administrative zones called ‘towns’. Allama Iqbal and Gulberg towns were selected for the study. Study was conducted during the month of September 2011, at the peak of epidemic Materials and Methods: The study was focused on densely populated 6 areas and a total of 219 household were randomly selected and interviewed and all information stored in a structured Proforma. Results: Among 219 households, showed that electronic media was the most common source of information within the community, followed by Friends and family. Areas of deficit knowledge were information about vector and its biting time and seasonal prevalence. The identified deficit areas of practices were keeping water storage tanks uncovered and less use of insecticides. Whereas, negative attitude noted was about elimination of larval breeding sources. Conclusion: Overall level of knowledge and practices were low however, study showed positive attitude of community toward Dengue prevention.